Comparison of a new tumour marker, CA 19-9, with alpha-fetoprotein and carcinoembryonic antigen in patients with upper gastrointestinal diseases. Issue 2 (February 1984) - Jalanko, H; Kuusela, P; Roberts, P; Sipponen, P; Haglund, C A; Mäkelä, O
Abstract : Serum CA 19-9 antigen concentrations were measured in 246 patients with benign and histologically confirmed malignant gastrointestinal diseases. The CA 19-9 concentration was above the upper limit of the normal range (0-37 U/ml) in 76% of patients with pancreatic carcinoma, 73% of patients with cholangiocarcinoma, 42% of patients with gastric carcinoma, and 22% of patients with hepatoma. High CA 19-9 concentrations were found mainly in patients with a metastasised cancer, whereas 71% of patients with a localised carcinoma had normal CA 19-9 concentrations. All of the patients with benign gastric diseases had normal CA 19-9 values. Moderately increased concentrations were found in 15-36% of the patients with benign pancreatic, liver, and biliary tract diseases. alpha-fetoprotein was a better marker for hepatomas than CA 19-9. CA 19-9 was better than carcinoembryonic antigen in differentiating malignant from benign diseases. The results indicate that the CA 19-9 assay is not completely specific for cancer but serves as a valuable adjunct, especially in the diagnosis of pancreatic carcinoma.